Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3109/08923973.2012.736520
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of all-transretinoic acid (ATRA) and enhanced activity of liposome encapsulated ATRA against inflammation and tumor-directed angiogenesis

Abstract: The purpose of this study was to investigate whether all-trans retinoic acid (ATRA) has antioxidant property. The study was also focused on its inhibitory effect on the acute and chronic inflammation and tumor-associated capillary formation in terms of angiogenesis in C57BL/6 mice after incorporated in liposome composed of distearoylphosphatidylcholine (DSPC/cholesterol). ATRA possesses a number of important biologic activities including oncostatic, antioxidant and immunostimulatory actions. Our study was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
(37 reference statements)
1
30
0
Order By: Relevance
“…A recent study has evaluated the antioxidant capacity of free retinoic acid by four different scavenging assays. The results showed significant scavenging activities in all these antioxidant assays comparable to the standard antioxidant (Siddikuzzaman & Grace, 2013). Although a high correlation between phenolic compounds and antioxidant capacity is expected, these results highlight the robustness of our approach to identify potential bioactive compounds.…”
Section: Use Of Correlation and Multivariate Statistical Analyses To supporting
confidence: 62%
“…A recent study has evaluated the antioxidant capacity of free retinoic acid by four different scavenging assays. The results showed significant scavenging activities in all these antioxidant assays comparable to the standard antioxidant (Siddikuzzaman & Grace, 2013). Although a high correlation between phenolic compounds and antioxidant capacity is expected, these results highlight the robustness of our approach to identify potential bioactive compounds.…”
Section: Use Of Correlation and Multivariate Statistical Analyses To supporting
confidence: 62%
“…Regardless of exact mechanisms, here we clearly showed that the ATRA-induced inhibition of tumor nodule formation correlated well with increased lifespan in lung tumor bearing mice. The drug dose used for the present study did not appear to be highly toxic to the B16F10 cells as we have reported earlier (35). By controlling the concentration of ATRA during the preparation of liposome, we could get liposome-encapsulated ATRA in which ATRA was loaded at about 85% yield.…”
Section: Discussionmentioning
confidence: 51%
“…ATRA has been reported to regulate the differentiation of serotonergic neurons (Fu et al, 2013), thereby promoting neuronal proliferation and regeneration (Hu et al, 1996;Lane andBailey, 2005, Ito andMorita, 1995), whereas chronic alcoholism adversely affects these processes and prevent adult neurogenesis (Valenzuela, 1997). Vitamin A and retinoids, which are redox-active molecules, exert antioxidant action at low concentration and pro-oxidant effects at high vitamin concentration (Lee et al, 2009;Siddikuzzaman, 2013). Our study involved supplementation of ATRA at low doses and the results clearly show reduction in oxidative stress due to ATRA supplementation, which may contribute to the observed protective effect of ATRA.…”
Section: Article In Pressmentioning
confidence: 53%
“…Vitamin A and retinoids are redox molecules and they have an antioxidant action at low concentration and pro-oxidant effects at high vitamin concentration (Lee et al, 2009;Siddikuzzaman, 2013). Supplementation of low dose retinoids against alcohol induced developmental damage was demonstrated in zebra fish embryos (Marrs et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation